Vocabulary instruction in an L2 culture course: the intersection of classroom discourse, materials, and instructor's choices in lexical focus-on-form episodes. Issue 1 (3rd April 2021) - Marcos Miguel, Nausica
ABSTRACT: Content courses for modern language majors at United States universities are a teaching environment where limited research on second language (L2) vocabulary instruction has taken place. On the surface, it may seem that instructors do not plan vocabulary instruction. This study explores this assumption as well as the potential for learning of specialised words by examining the classroom discourse and the curricular materials, e.g., readings and instructor-created PowerPoints, of an advanced Spanish L2 culture course. Ten consecutive classroom sessions, taught by an experienced instructor, were analysed. A corpus-based analysis was conducted to identify 27 specialised target words that could potentially be learned based on their high frequency of use in classroom discourse and in the materials. In addition, the instructor-initiated lexical focus-on-form episodes on the target words were analysed, exploring the connection between the materials and the instructor's pedagogical choices. For all lexical focus-on-form episodes, the materials prompted vocabulary instruction, mostly in a pre-emptive way. Since the target words were included in the teaching materials, instruction on these words could potentially be planned. That is, the dichotomy between planned and unplanned instruction is not such when including materials in the analysis.